Shakespeare and the Cleopatra/Caesar Intertext : Sequel, Conflation, Remake. - Hatchuel, Sarah (Rowman & Littlefield Pub. Group, 2011)
Is William Shakespeare's Antony and Cleopatra a sequel to the earlier Julius Caesar? If this question raises issues of authorship and reception, it also interrogates the construction of dramatic sequels: how does a playtext ultimately become the follow-up of another text? This book explores how dramatic works written before and after Shakespeare's time have encouraged us to view Shakespeare's Julius Caesar and Antony and Cleopatra as strongly interconnected plays, encouraging theirsequelization in the theater and paving the way toward the filmic conflations of the twentieth century. Blending.